2011
DOI: 10.1074/jbc.m110.190470
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3γ Inhibition of MDMX-mediated p21 Turnover Independent of p53

Abstract: The stability of p21, a cyclin-dependent kinase inhibitor, is highly regulated by various protein molecules through the cell cycle and in response to extracellular signals. One of the p21 regulators is MDMX, which can directly bind to p21 and mediate its proteasomal degradation in an ubiquitination-independent fashion. The fact that 14-3-3␥ binds to the MDMX domain adjacent to p21 binding suggests that this 14-3-3␥ may affect MDMX-mediated p21 proteasomal turnover. Indeed, we found that overexpression of 14-3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 46 publications
2
13
1
Order By: Relevance
“…As a matter of fact, upon overexpression of MEF2C, we observed an induction of 14-3-3g, Gadd45b and p21 transcripts, encoding inhibitors of the CYCLIN B1/CDK1 kinase. 24,[52][53][54][55][56] These genes have a role in the G2-M checkpoint both in normal cell cycle progression and in response to DNA damage. We also found that failure of MEF2C degradation correlates with an increase in the cytoplasmic inactive fraction of CYCLIN B1.…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, upon overexpression of MEF2C, we observed an induction of 14-3-3g, Gadd45b and p21 transcripts, encoding inhibitors of the CYCLIN B1/CDK1 kinase. 24,[52][53][54][55][56] These genes have a role in the G2-M checkpoint both in normal cell cycle progression and in response to DNA damage. We also found that failure of MEF2C degradation correlates with an increase in the cytoplasmic inactive fraction of CYCLIN B1.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the cell viability changes for both miRNAs were similar to the MDM4 siRNA-positive control, we believe the latter scenario is likely. Besides p53, MDM4 interacts with several other proteins including p21, a cyclin-dependent kinase inhibitor whose expression is associated with reduced proliferation in prostate cancer (Jin et al 2008, Lee & Lu 2011, Peng et al 2013, the transcription factor E2F1, which is known to play a role in cell-cycle regulation in prostate cancer (Strachan et al 2003, Lee et al 2013, the E3 ubiquitin ligase MDM2 that also harbours polymorphisms associated with the risk of prostate cancer (Badciong & Haas 2002 and both Smad3 and Smad4, which are major activating components of the transforming growth factor-b (TGF-b) signalling pathway that has been shown to repress growth in prostate cancer (Kadakia et al 2002, Bjerke et al 2014, Mishra et al 2014. As MDM4 probably plays a role in cancer susceptibility and progression via multiple pathways, further study is required to assess the prostatespecific effects of miRNA-mediated MDM4 levels on each of these pathways.…”
Section: Discussionmentioning
confidence: 99%
“…MDM4 interacts with a variety of proteins in different human cell lines, such as p21, 14-3-3gamma, ASPP, ARF, p300, Smads, and RB [19,[21][22][23][40][41][42], suggesting that it has p53-independent functions. Also, MDM4 promotes genomic instability by associating with Nbs1 to promote cell transformation [25].…”
Section: Mdm4 Has P53-independent Functions In Vivomentioning
confidence: 99%
“…Moreover, the fact that some tumours have both high MDM4 levels and TP53 mutations suggests possible p53-independent functions of MDM4. Besides binding to p53 and Mdm2, Mdm4 also interacts with other proteins, such as p21, 14-3-3gamma, ARF, HAUSP, and Nbs1 [19][20][21][22][23][24][25], suggesting that Mdm4 has p53-independent functions. Specifically, Mdm4 promotes genomic instability and increases cell transformation independently of p53 and Mdm2 by interacting with Nbs1 [25], further suggesting that Mdm4 has a p53-independent function.…”
Section: Introductionmentioning
confidence: 99%